Working for God? Evaluating Service Delivery of Religious Not-for-Profit Health Care Providers in Uganda - Reinikka, Ritva; Svensson, Jakob (World Bank, Washington, DC, 2014)
Reinikka and Svensson exploit a unique micro-level data set on primary health care facilities in Uganda to address the question: What motivates religious not-for-profit (RNP) health care providers? The authors use two approaches to identify whether an altruistic (religious) effect exists in the data. First, examining cross-section variation, they show that RNP facilities hire qualified medical staff below the market wage, are more likely to provide propoor services and services with a public good element, and charge lower prices for services than for-profit facilities, although they provide a similar (observable) quality of care. RNP and for-profit facilities both provide better quality care than their government counterparts, although government facilities have better equipment. These findings are consistent with the view that RNP facilities are driven in part by altruistic concerns and that these preferences matter quantitatively. Second, the authors exploit a near natural experiment in which the government initiated a program of financial aid for the RNP sector. They show that financial aid leads to more laboratory testing of suspected malaria and intestinal worm cases, and hence higher quality of service and lower prices, but only in RNP facilities. The findings suggest that working for God matters.